Implementation of SECAR (Senam Ceria) Through Aerobic Kids in Elementary School Laboratory Nusantara PGRI Kediri University - Nur Ahmad Muharram; Moh. Nur Kholis; Dhedhy Yuliawan; Slamet Junaidi; Septyaning Lusianti (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
Sports is one form of activity in improving the physical quality of humans. There are many ways to develop physical motor skills of students one of them with aerobic exercise. Gymnastic movements can support students' physical development such as strength and muscular endurance. Aerobic Kids Gymnastics is a type of rhythmic gymnastics whose movements are adjusted to the age and development of elementary school students. The movements of dancing, jumping, spinning like mimicking animal movements make pre-school age students more eager to follow it. Good sports activities for elementary school students have characteristics; (1) giving various experiences of movement (multilateral training); (2) stimulates the development of all five senses; (3) developing imagination (fantasy); and (4) moves to the rhythm (song) or story. From the characteristics of sports for elementary school students, the writer tries to pack in the form of a fun aerobic kids gymnastics so that students feel interested to follow and have fun. Gross motor development is very important for students, especially elementary school students. The development of gross motor skills in students needs the assistance of educators in elementary school educational institutions, namely in terms of what is helped, how to help the right (appropriate), how the types of exercises that are safe for students according to age stages and how physical activity of gross motoric fun the student. SECAR through Aerobic Kids Gymnastics with UN PGRI Kediri Primary School Laboratory School is expected to be able to improve students' gross motor skills and motivate educators to be creative according to students' age in an effort to improve students' gross motor skills. This activity is carried out directly by conducting a demonstration of Aerobic Kids' gymnastics in sports learning. The subjects of this study were 17 students and teachers of the Elementary School Laboratory of PGRI Kediri School. The results of this activity show that there is good enthusiasm from students and teachers in participating in SECAR in the Aerobic Kids Gymnastics Movement.